Kedudukan Akta Di Bawah Tangan Yang Membatalkan Akta Notariil - Sharon Eunice (Darma Cendika Catholic University, 2019)
This article aims to determine the position of the privately made deed and notarial deed. In this case, the District Court Decision Number 738 / Pdt.6 / 2016 / PN.Sby stated that the deed of sale and purchase was canceled between Mrs. Hierawati and Mrs. Maria Magda. The District Court's decision is corroborated by the Decision of the High Court Number 83 / PDT / 2018 / PT. SBY. A sale and purchase deed from a notary is an authentic deed that has perfect and binding proof power (Article 1867 KUHPer), while the evidentiary power of a privately made deed is lost if denied by the party. In this case, the defendant does not acknowledge the contents of the statement. In accordance with the jurisprudence from the Supreme Court of the Republic of Indonesia Number 167 K / SIP / 1959, it is stated that a privately made deed is a binding proof is its content is acknowledged by the party. However, if a privately made deed is denied by one of the parties, it lost its evidentiary power. A sale and purchase deed from a notary cannot be canceled by a statement which is a privately made deed.